SEBARAN GUA ARKEOLOGIS DI KECAMATAN PALIYAN KABUPATEN GUNUNGKIDUL DENGAN MENGGUNAKAN ANALISIS TETANGGA TERDEKAT (NEAREST NEIGHBOURHOOD ANALYSIS) - Harry Octavianus Sofian (Balai Arkeologi Yogyakarta, 2011)
Gunung Sewu karst area has attracted the attention archaeologists since the Dutch colonial era to the present. One of the karst area is located Paliyan District, Gunungkidul Regency. Based on research conducted by Harry Octavianus Sofian in year 2007, there were at least 11 caves and rockshelter as a potential residential dwelling. This paper will discuss and look for patterns of spatial distribution of caves and archaeological potential rockshelter as an ancient settlement in the District Paliyan using Nearest Neighbor Analysis (Analisis Tetangga Terdekat) manually and use Neighborhood Statistic analysis contained in the Arc View software.